Spreadsheet-Based Program for Alignment of Overlapping DNA Sequences - Ramaswamy Anbazhagan; Edward Gabrielson (BioTechniques)
Molecular biology laboratories frequently face the challenge of aligning small overlapping DNA sequences derived from a long DNA segment. Here, we present a short program that can be used to adapt Excel® spreadsheets as a tool for aligning DNA sequences, regardless of their orientation. The program runs on any Windows® or Macintosh® operating system computer with Excel 97 or Excel 98. The program is available for use as an Excel file, which can be downloaded from the BioTechniques Web site. Upon execution, the program opens a specially designed customized workbook and is capable of identifying overlapping regions between two sequence fragments and displaying the sequence alignment. It also performs a number of specialized functions such as recognition of restriction enzyme cutting sites and CpG island mapping without costly specialized software.